A Project Report on Efficient Resource Sharing in Cloud - CHANDRAKANTH, GAJENDRA GOWDA, MAHESH and ANUP PATIL (2013)
INTERNAL GUIDE: SIVAGAMA SUNDARI G, MVJCE
Keywords: Efficient Resource Sharing in Cloud